E-Catalog V6: The Manifestation of Local Government Accountability in the Procurement of Goods and Services - Jovan Christy Nugraha Labiro; Rudy Usman; Ridwan Ridwan; Muhammad Ilham Pakawaru (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the accountability of goods and services procurement through the implementation of E-Catalog Version 6 at the Regional Development Planning Agency (BAPPEDA) of Central Sulawesi Province, specifically in the preparation of performance achievement reports. The study employs a qualitative approach using data collection techniques such as documentation and interviews. Data sources include the 2025 E-Catalog Version 6 policy document, goods and services procurement documents, and interview results with the Commitment-Making Official (PPK), Technical Activity Implementation Official (PPTK), and Goods and Services Manager. The research findings indicate that the implementation of E-Catalog Version 6 enhances transparency, accountability, and procurement efficiency through an integrated digital system that can be monitored in real-time. Simplified features, enhanced security, and the addition of administrative documents such as the Terms of Reference (TOR) support administrative orderliness and facilitate audits. However, implementation still faces challenges such as delays in account verification, limitations in network infrastructure, human resource capacity, and suboptimal integration of digital payments. The findings contribute to improving service quality through the integration of modern technology that facilitates service delivery to the public via local government procurement of goods and services.